Weight stigma and mental health symptoms: mediation by perceived stress - Figueroa, David G.; Murley, William D.; Parker, Jordan E.; Hunger, Jeffrey M.; Tomiyama, A. Janet (Frontiers in Psychiatry, 2025)
Prior research has established that weight stigma, or social devaluation based on an individual’s body size or weight, is directly related to greater depressive and anxiety symptoms. In this investigation, we apply the Cyclic Obesity/Weight-Based Stigma model to investigate if the association between weight stigma and poor mental health is mediated by greater perceived stress. We analyzed data from a census-matched sample (N=1,993) of the U.S. on age, race/ethnicity, gender, income, and census-region. Issues with missing data and mediation models were addressed using a Bayesian multiple imputation approach. Analyses controlled for Body Mass Index and sociodemographic variables as covariates. Weight stigma was directly associated with greater depressive and anxiety symptoms. Moreover, the relationship between weight stigma and greater depressive and anxiety symptoms was mediated by greater perceived stress. Perceived stress explained 37% of the relationship between weight stigma and mental health outcomes, even after accounting for Body Mass Index. These results provide evidence for weight stigma as an important psychosocial stressor that contributes to poor mental health outcomes.